The Influence of Electronic Payment System on Economic Growth and Inflation as a Moderation Variable in Indonesia 2019-2023 - Ery Rahmawati; Hasanudin Hasanudin (Universitas KH. Abdul Chalim Mojokerto, 2024)
The purpose of this study was to analyze and obtain empirical evidence of the effect of the Electronic Payment System on Economic Growth and Inflation as a Moderating Variable in Indonesia in 2019-2023. The research was conducted in 34 provinces using a purposive sampling method in selecting samples for the 2019-2023 period. The data analysis method used is the panel data regression method using Moderate Regression Analysis (MRA) on Stata 17.0 application software. The results of this study state that the volume of electronic money has a significant positive direct effect on economic growth in provinces in Indonesia for the period 2019-2023. The volume of debit cards has a significant positive direct effect on economic growth in provinces in Indonesia for the period 2019-2023. The variable volume of credit cards has a significant positive direct effect on economic growth in provinces in Indonesia for the period 2019-2023. The inflation variable has a positive and insignificant effect in moderating the volume of electronic money on economic growth in provinces in Indonesia for the period 2019-2023. The inflation variable has a significant negative effect in moderating the volume of debit cards on economic growth in provinces in Indonesia for the period 2019-2023. The inflation variable has a positive and insignificant effect in moderating the volume of credit cards on economic growth in provinces in Indonesia for the period 2019-2023.